The role of 3-OH in the self-assembly of pharmaceutical cocrystals of dihydroflavonol with 4, 4′-bipyridine. (11th January 2021) - Liu, Lixin; Liu, Moqi; Zhang, Yunan; Yin, Hemei; Su, Xin; Zhang, Qiang; Feng, Yanru; Guo, Yingxue; Zou, Dongyu; Liu, Yingli
Abstract : The 3-OH group of nonplanar dihydroflavonols participates in the formation of hydrogen bonds with BPY, thereby forming cocrystals with different structures. Abstract : In order to further explore the role of hydroxyl in the synthesis of pharmaceutical cocrystals and with a view to improving physicochemical properties of flavonoids, two dihydroflavonols in which 3-OH is exposed and cross-conjugated system is destroyed (dihydroquercetin (DHQ) and dihydromyricetin (DMY)) were selected to combine with 4, 4′-bipyridine (BPY) to explore the role of 3-OH of dihydroflavonol in synthetic processes of pharmaceutical cocrystals of dihydroflavonol. As a result, two new pharmaceutical cocrystals of dihydroflavonol with BPY (2(C15 H12 O7 )·3(C10 H8 N2 ), DHQ·BPY); and (C15 H12 O8 ·2.5(C10 H8 N2 ), DMY·BPY) have been synthesized and characterized. Structure analysis revealed that in DHQ·BPY the intermolecular hydrogen bond formed by 3-OH of DHQ with BPY participated in the formation of motifs R 6 6 (44) to form the cocrystal with helical structure. In DMY·BPY, the intermolecular hydrogen bond formed by 3-OH of DMY with BPY connects adjacent motifs R 4 4 (38) to form the cocrystal with layered structure. The solubility of DHQ·BPY is lower than that of pure DHQ, possibly because the helical structure of DHQ·BPY is tighter than that of nonplanar DHQ, which limits the entry of water molecules. Compared with nonplanar DMY, DMY·BPY with layered structure is more likely to allow water molecules to enter, which leads to the solubility of DMY·BPY being higher than that of pure DMY. The hygroscopic stabilities of DHQ·BPY and DMY·BPY are better than that of their corresponding parent APIs. It is possible that in DHQ·BPY and DMY·BPY, most of the hydroxyls in the A, B and C rings of DHQ and DMY are involved in the formation of intermolecular hydrogen bonds, which means the hydroxyls of DHQ·BPY and DMY·BPY are difficult to combine with moisture. This work shows that 3-OH of nonplanar dihydroflavonol can form hydrogen bonds with BPY after the destruction of the cross-conjugated system, and then form cocrystals with helical structure and layered structure, thereby having an effect on the properties of APIs. This successful study implies that the role of 3-OH in the self-assembly process of flavonoid pharmaceutical cocrystals and improving the physicochemical properties of flavonoid APIs should not be neglected in the future.